PERFORMANCE OF MALE MICE (MUS MUSCULUS) AGE 28-63 DAYS IN THE COTE WITH HUSK LAYER, SAND LAYER, AND ZEOLITE LAYER WITH PARTITION OR NOT - Rakhmadi I.; Muladno Muladno; H. C. H. Siregar; Pollung H. Siagian (Jurnal Zeolit Indonesia, 2009)
The study aimed to analyze the effect of different layer types with pertition or not against perfomence male mice ages 28-63 days and to find out the information of ammonia on different layer cotes. The parameters measured were feed intake BK, dringking water, beginning and ending BW, ADG, feed convertions, mortality, and ammonia on cages. CRD designs was used in 3 x 2 factorial experiment, the first factor are types of layer (huks, sand, and zeolite) and the seconds factor are partition of layer (without insulation and section). The data obtained were analyzed with ANOVA if there are a real result, followed by Tukey test appeal. The data which not suitabele with the parameters was analyzed with Kruskal-Wallis test, whereas the ammonia on cote described descriptively. The result showed that different types of layer most significant (p